Toward Ubiquitous Operating Systems: Lessons from the Field. - Luo, Chu; Kostakos, Vassilis (Communications of the ACM, 2025)
This article explores ubiquitous operating systems (UOS) for mobile devices for ease in communication between two or more mobile devices. UOS can be enabled by a system-level infrastructure serving all applications to avoid repetitive coding of communication paths in cross-device tasks and allowing for the ease of adding new applications to the system. Four challenges and recommendations for each are provided by the authors for UOS including clock synchronization and device-system interaction.